Clinical and genetic features in Italian Bietti crystalline dystrophy patients. Issue 2 (6th December 2012) - Rossi, Settimio; Testa, Francesco; Li, Anren; Yaylacioğlu, Fulya; Gesualdo, Carlo; Hejtmancik, J Fielding; Simonelli, Francesca
Abstract : Aim: The aim of the study was to describe the clinical and genetic features of 15 Italian patients with Bietti crystalline dystrophy (BCD). Methods: All study participants underwent a complete ophthalmological examination, including standard electroretinogram (ERG), optical coherence tomography, microperimetry, autofluorescence and multifocal electroretinogram. The 11 exons of the CYP4V2 gene were sequenced. The effect of mutations on protein function was estimated by a combination of web based programs. Results: 15 patients (eight women, 7 men, aged 29–60 years) with BCD were recruited into this study. Sequencing of CYP4V2 revealed nine sequence variants in four unrelated families and six isolated individuals with BCD. Seven of these variants were novel. Among the patients, even with the same genotype, considerable variability in phenotypic expression with different degrees of accumulation of the typical intraretinal crystalline deposits was detected. Moreover, we found that more than 50% of patients had recordable standard ERG responses and in two patients the responses were within normal limits after 20 years of symptom onset. Conclusions: In conclusion, we have reported seven new mutations and illustrated the large range of genotypic and phenotypic variability in BCD, highlighting the lack of a clear genotype–phenotype correlation and underlining the existence of less severe clinical manifestations, probably linked to relatively mild mutations.